852Lead abandonment and subcutaneous implantable cardioverter-defibrillator (S-ICD) implantation in a cohort of patients with ICD lead malfunction. (18th June 2020) - Russo, V; Viani, S; Migliore, F; Tola, G; Bisignani, G; Biffi, M; Dello Russo, A; Sartori, P; Rordorf, R; Ottaviano, L; Perego, G B; Papa, A; et al.
Abstract: Funding Acknowledgements: NO FUNDING OnBehalf: Rhythm Detect Registry Background: Currently, when an implantable-cardioverter defibrillator (ICD) lead becomes nonfunctional, a class IIa recommendation exists for either lead abandonment or for removal. The benefits of removal include creation of an access for insertion of a new lead. However, the subcutaneous ICD (S-ICD) does not require the insertion of any leads into the cardiovascular system, and may represent an additional option for patients not requiring pacing. Purpose: To report outcomes associated with a strategy of lead abandonment and S-ICD implantation in the setting of lead malfunction. Methods: We analyzed all consecutive patients who underwent S-ICD implantation after abandonment of malfunctioning leads and we compared outcomes with those of patients who underwent transvenous extraction and subsequent reimplantation of a single-chamber transvenous ICD (T- ICD). Results: 43 patients were implanted with an S-ICD after abandonment of malfunctioning leads, while in 62 patients extraction and subsequent reimplantation of a T-ICD. The two groups were comparable (Age 55 ± 16 vs. 54 ± 33years, BMI 26 ± 3 vs. 24 ± 4kg/m2, LVEF 43 ± 15 vs. 48 ± 8%). S-ICD defibrillation test success rate at implantation was 96% at 65J. In the extraction group, no major complications were reported during extraction, while the procedure failed and an S-ICD was implanted in 4 patients. During a median follow-up of 21 months, the rate of major complications was not higher in the S-ICD group than in the T-ICD group (HR 1.07; 95%CI 0.29–3.94; P = 0 .912; Figure), as well as the rate of minor complications (HR 2.13; 95%CI 0.49–9.24; P = 0 .238). Conclusions: In case of ICD lead malfunction, extraction prevents potential long-term risks of abandoned leads, e.g. increased complications for a possible future mandatory extraction indication such as infection, and allows magnetic resonance imaging. Nonetheless in this series, the strategy of lead abandonment and S-ICD implantation appeared to be feasible and safe with no significant increase in adverse outcomes for patients not requiring pacing and may represent an option in selected clinical settings (very high risk or failed extractions, older patients, etc.). Longer follow-up studies are needed to fully understand the potential risks of lead abandonment.